Fiscal Policy and Economic Activity During Recessions in Advanced Economies - Schimmelpfennig, Axel (IMF Working Papers; Working Paper, 2002)
Using data for advanced economies, this paper investigates whether factors identified in the theoretical and empirical literature explain the effectiveness of fiscal policy in responding to recessions. The results are informative about the fiscal response to recessions but provide only a partial explanation of the impact of fiscal policy on economic activity. Overall, it would appear that fiscal multipliers are very small.